Chenodeoxycholic Acid Modulates Bile Acid Synthesis Independent of Fibroblast Growth Factor 19 in Primary Human Hepatocytes - Johansson, Helene; Søndergaard, Jonas Nørskov; Jorns, Carl; Kutter, Claudia; Ellis, Ewa C. S. (Frontiers in Endocrinology, 2021)
Bile acids (BAs) are detergents essential for intestinal absorption of lipids. Disruption of BA homeostasis can lead to severe liver damage. BA metabolism is therefore under strict regulation by sophisticated feedback mechanisms. The hormone-like protein Fibroblast growth factor 19 (FGF19) is of interest in aspect of keeping BA homeostasis by down regulating BA synthesis. Here, the impact of both FGF19 and chenodeoxycholic acid (CDCA) on primary human hepatocytes was investigated and a possible autocrine/paracrine function of FGF19 in regulation of BA synthesis evaluated. Primary human hepatocytes were treated with CDCA, recombinant FGF19 or conditioned medium containing endogenously produced FGF19. RNA sequencing revealed that treatment with CDCA causes deregulation of transcripts involved in BA metabolism, whereas treatment with FGF19 had minor effects. CDCA increased FGF19 mRNA expression within 1 h. We detected secretion of the resulting FGF19 protein into medium, mimicking in vivo observations. Furthermore, medium enriched with endogenously produced FGF19 reduced BA synthesis by down regulating CYP7A1 gene expression. However, following knockdown of FGF19, CDCA still independently decreased BA synthesis, presumably through the regulatory protein small heterodimer partner. In summary, we show that in primary human hepatocytes CDCA regulates BA synthesis in an FGF19 independent manner.